Development of a novel multi-epitope peptide vaccine candidate against Mycobacterium tuberculosis using reverse vaccinology: A promising strategy for enhanced immunoprotection - Hasan, Nur AHM.; Giri-Rachman, Ernawati A.; Nugrahapraja, Husna (Narra Sains Indonesia, 2026)
Tuberculosis (TB) is a leading cause of death worldwide, caused by Mycobacterium tuberculosis (Mtb). The existing Bacillus Calmette-Guerin (BCG) vaccine has limitations, especially its reduced effectiveness in adults. This research focuses on developing a multi-epitope Mtb vaccine candidate through reverse vaccinology, aiming for a more effective and widely applicable solution. The study used the Vaxign2 pipeline to identify Mtb antigenic proteins, including PPE35, mpt83, mrsA, and rplK. Cytotoxic T cells (CTL), helper T cells (HTL), and B-cells, were predicted and selected based on their antigenicity, non-allergenicity, and non-toxicity. The chosen epitopes from these proteins, 4 CTL, 1 HTL, and 1 B cell epitope, were assembled into a multi-epitope vaccine construct, incorporating the adjuvant PADRE and linkers (EAAAK, AAY, and GPGPG). The vaccine candidate has a molecular weight of 10.68 kDa, with stability, hydrophilicity, and solubility confirmed. Its 3D structure was validated for quality and accuracy. Docking and molecular dynamics simulations with immune receptors TLR2 and TLR4 showed strong, stable interactions. The global population coverage of the vaccine candidate was reaching 98.19%. In silico cloning into the pET30a(+) vector in Escherichia coli BL21(DE3) was successful, with codon optimization (CAI: 0.98) and a GC content of 54.6%. Immunity simulations indicated enhanced activation of antigen-presenting cells, CTL, HTL, B cells, and antibody production. Overall, this study suggests vaccine candidate is a promising multi-epitope vaccine candidate, warranting further in vivo testing, including protein expression in E. coli.